2022
DOI: 10.1177/03936155221118098
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-to-lymphocyte ratio associated with the clinicopathological features and prognostic value of breast cancer: A meta-analysis

Abstract: Objective The association of platelet-to-lymphocyte ratio (PLR) with the clinicopathological features and prognosis in patients with breast cancer was evaluated. Method Related studies were searched from PubMed, Embase, Cochrane Library, and Web of Science up to July 1, 2021. Then, basic characteristic and prognostic data were extracted from the included studies. We synthesized and compared primary outcomes such as overall survival. Subgroups analyses in pathology, geographical area, follow-up time, and sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…For example, high NLR and PLR were associated with shorter overall survival and disease-free survival, while low LMR was associated with improved prognosis [12,14]. Besides, the elevated PLR was related to the risk of lymph node metastasis and distant metastasis [13]. In addition, PLR was an independent factor for predicting pCR after NAC for BC, and patients with low PLR achieved higher pCR rates [15][16][17].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, high NLR and PLR were associated with shorter overall survival and disease-free survival, while low LMR was associated with improved prognosis [12,14]. Besides, the elevated PLR was related to the risk of lymph node metastasis and distant metastasis [13]. In addition, PLR was an independent factor for predicting pCR after NAC for BC, and patients with low PLR achieved higher pCR rates [15][16][17].…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have shown that PLR can be used as a predictor and prognostic factor of treatment response to NAC for BC. Low PLR was associated with prolonged overall survival and diseasefree survival [12], while high PLR was associated with increased risk of lymph node and distant metastasis in BC patients [13]. PLR can also predict the pathological response of BC patients after NAC.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…33 In a meta-analysis of 7484 patients with BC, elevated platelet-lymphocyte ratios were associated with a poor BC prognosis and a high risk of distant metastasis. 34 In this study, several blood parameters were associated with TLSs, including LYMPH%, MONO %, BASO%, and PLT.…”
Section: Discussionmentioning
confidence: 61%
“…Many studies have found that systemic inflammatory responses affect the occurrence and development of malignant tumors by regulating the biological microenvironment[ 29 - 33 ]. Based on this concept, several simple and stable inflammatory markers have been shown to be associated with prognosis in malignancy, including platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index, neutrophil-to-lymphocyte ratio (NLR), prognostic nutritional index and Glasgow Prognostic Score[ 34 - 38 ]. Recently, a novel inflammatory marker, the C-reactive protein (CRP) to albumin ratio (CAR), has been reported as an independent prognostic factor in various malignancies.…”
Section: Introductionmentioning
confidence: 99%